2022
DOI: 10.17159/2411-9717/1535/2022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica concentration on degree of sintering of chromite-silica ladle well filler sand based on South African raw materials

Abstract: During steelmaking, one important factor for production efficiency is the free opening of the ladle nozzle during continuous casting. Free opening occurs when the well filler sand and the steel flow freely when the slide gate is opened. Well filler sands are used for the slide gate of a ladle to separate the slide gate refractory and the molten steel. The well filler sand is partially sintered by the heat of the molten metal, which can result in the ladle nozzle failing to open if the sand is not sintered to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The effect of Al in steel has also been confirmed in the case of chromite filler sand, [ 13–15 ] and it has been observed that the liquid phase can react with dissolved Al in liquid steel, leading to an increase in Al 2 O 3 content. Previous research [ 33 ] has indicated that the Al 2 O 3 crucible does not significantly impact the experimental results. In the current study, all steels contain 2 mass% Al, but the liquid phase has an entirely different content of Al 2 O 3 , as shown in Table 5.…”
Section: Discussionmentioning
confidence: 96%
“…The effect of Al in steel has also been confirmed in the case of chromite filler sand, [ 13–15 ] and it has been observed that the liquid phase can react with dissolved Al in liquid steel, leading to an increase in Al 2 O 3 content. Previous research [ 33 ] has indicated that the Al 2 O 3 crucible does not significantly impact the experimental results. In the current study, all steels contain 2 mass% Al, but the liquid phase has an entirely different content of Al 2 O 3 , as shown in Table 5.…”
Section: Discussionmentioning
confidence: 96%
“…A mixture of refractory raw materials, called "filler sand", is used to protect ladle slide gate from the liquid steel during refining process (Figure 1) [1]. The top layer of the filler sand needs to be sintered in an appropriate degree so that when the slide gate nozzle is opened, the sintered layer needs to break due to the pressure of the liquid metal, allowing the liquid steel to flow out [2]. This is called "ladle free opening".…”
Section: Introductionmentioning
confidence: 99%